Model of Transferring Missions for Prevention and Control of Diseases and Health Risks of Department of Disease Control to Local Administrative Organizations - Bunchum, Achara; Pinyopornpanich , Benjamaporn (Disease Control Journal, 2024)
The Act on Decentralization Plans and Procedures for Local Government Organizations, B.E. 2542 (A.D.1999), assigns the Provincial Administrative Organizations (PAOs) to oversee the communicable disease prevention and control missions. This study aimed to evaluate the readiness of PAOs and examine the role of the Department of Disease Control (DDC), in order to propose a model for transferring the DDC’s missions on disease prevention and control to the Local Government Organizations (LGOs). The study covered 32 provinces, 86 executives were recruited to complete the questionnaires. Eight executives were subjected to the in-depth interview. The missions’ transferring model was referred to the 6 Building Blocks of a health system. The results revealed that 93% of respondents highlighted the necessity of redefining PAO roles in disease prevention and control, as well as health related threat management. The most critical areas requiring immediate attention were i) emerging communicable diseases such as COVID-19 (94.2%), ii) non-communicable diseases such as diabetes, hypertension, and cardiovascular diseases, and iii) occupational related diseases (80.2%). The overall readiness of PAOs to responsible for these missions was rated as moderate (x=2.24), where the aspect of leadership and governance were reported as well as the most readiness (x=2.65), followed by the financial aspect (x=2.51), and information and technology systems were found the least preparedness(x=1.86). In addition, the establishment of emergency operations centers (EOCs) mechanism at the sub-district level showed a low readiness score (x=1.79). Regarding the readiness of the disease prevention and control transferring missions, the executives’ opinions suggested that this depended on the leaders’ visions and reliance. In case of decentralisation, the local areas are able to self-manage and resolve the problems with support from DDC. DDC will focus on building up the capacity of local personnel so as to support LGOs. This transition should be accompanied by increased investment in developing robust management system of disease prevention, control, and health related threats, as well as information systems for effective emergency responses and outbreaks.